DC Motor Controller Using Full State Feedback - Setiawan, Naufal Rahmat; Ma'arif, Alfian; Widodo, Nuryono Satya (Peneliti Teknologi Teknik Indonesia, 2023)
This paper discusses the implementation of a full state feedback control system on DC motors to stabilize the speed of DC motors and fight the disturbances given to DC motors. Modern controls such as full state feedback use 2 sensor inputs, namely the Hall effect speed sensor OH42E and the INA219 current sensor and use 3 parameters namely K1 (Constant 1), K2 (Constant 2), and KI (Integral Constant) in designing the controller, the goal is to get a good system response according to the desired design specifications. The test was carried out with a hardware-in-the-Loop (HIL) scheme which uses an Arduino microcontroller as a DC motor plant control device in the form of a control mathematical model entered in the Arduino IDE software and by trial and error to find the desired response value. The test results showed that at the values of K1=1, K2=1, KI=0.9, a stable system response was obtained with tr(s)=3, ts(s)=4, and Os(%)=7% The addition of an integral constant () value affects a short rising time but is inversely proportional to a high overshoot value as well. Varying the values of K1 and K2 as multipliers on the sensor values has an impact on the stability of the system response or oscillations. The stability of this system response indicates that full state feedback can be relied upon as a control system.